The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10750-008-9527-5
|View full text |Cite
|
Sign up to set email alerts
|

Salinity as a driver of aquatic invertebrate colonisation behaviour and distribution in the wheatbelt of Western Australia

Abstract: To understand how environmental change will modify community assembly and the distribution of organisms it is valuable to understand mechanisms that drive the occurrence of organisms across the landscape. Salinisation of agricultural land in southwest Western Australia, as a result of land clearing, is a widespread environmental change, which threatens numerous taxa, but provides an opportunity to elucidate such mechanisms. Although salinisation affects terrestrial fauna and flora, the greatest impacts are see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
3
21
0
1
Order By: Relevance
“…were strongly associated with vegetated freshwater pools (Medlock et al, 2005). Several studies have demonstrated that ovipositing mosquitoes from different genera (Culiseta, Aedes, Anopheles) could tolerate a variety of salt concentrations but the larvae failed to develop correctly in salt water (Bentley & Day, 1989;Carver et al, 2009). In the case of Coquillettidia, survival of the larvae might be affected by salt water, as suggested by laboratory experiments which have shown that egg hatching and development of larvae were perturbed by salt water (EID Montpellier-France, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…were strongly associated with vegetated freshwater pools (Medlock et al, 2005). Several studies have demonstrated that ovipositing mosquitoes from different genera (Culiseta, Aedes, Anopheles) could tolerate a variety of salt concentrations but the larvae failed to develop correctly in salt water (Bentley & Day, 1989;Carver et al, 2009). In the case of Coquillettidia, survival of the larvae might be affected by salt water, as suggested by laboratory experiments which have shown that egg hatching and development of larvae were perturbed by salt water (EID Montpellier-France, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on aquatic invertebrates in wetlands throughout inland southwest WA have demonstrated that salinity is the primary factor influencing community structure (Carver et al 2009d;Kay et al 2001;Pinder et al 2004). Secondary saline wetlands had significantly different and relatively depauperate macroinvertebrate fauna compared to remaining freshwater wetlands.…”
Section: Ecological Impact Of Dryland Salinitymentioning
confidence: 99%
“…Mosquitoes are known to respond a range of environmental conditions, including disturbance, which can have their colonization (Williams, 2006;Carver et al, 2009). In India, climate change represents as additional stress on ecological and socioeconomic systems that are already facing tremendous pressures due to rapid urbanization, industrialization and economic development (Sumana et al, 2006).…”
Section: Introductionmentioning
confidence: 99%